Seeking Time Within Time: Exploring the temporal constraints of women teachers’ experiences as graduate students and novice researchers - Mitton Kukner, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
The primary focus of this qualitative study is an inquiry into three female teachers’ experiences as novice researchers. Over the course of an academic year I maintained a focus upon participants’ research experiences and their use of time as they conducted research studies. Delving into the temporal constraints that informed participants’ research experiences provided insights into competing demands shaping their understanding of research. In light of current performance accountability measures monitoring the ways teachers are using their professional time, this study provides new ways to consider the multiple challenges and gendered inequities female teachers are navigating in their efforts to professionally develop and learn.